MEMBANGUN PRIVATE CLOUD DENGAN NEXTCLOUD DAN UBUNTU UNTUK SOLUSI UMKM - Hendri Hendri; Subur Anugerah (Universitas Mulia, 2024)
Virtualization technology has developed rapidly with alternative information technology services. Virtualization uses available hardware resources more efficiently, providing a more flexible and cost-effective running Cloud Computing platform. Ubuntu Server 22.04.4 LTS provides a reliable and stable platform for running several server services, including Nextcloud. Nextcloud is a popular Cloud application that supports many features ranging from file storage, document collaboration, calendaring, and many other functions that can be accessed through a web interface and is available for free. Meanwhile, business actors who are part of MSMEs (Micro, Small and Medium Enterprises) are currently also growing after the pandemic. MSME business actors use information technology devices for various purposes to support their business activities, one of which is by using Cloud Computing services. By explaining the implementation steps for building a Nextcloud server virtualization machine as a service on a LAN (Local Area Network), it is hoped that this will be a solution to overcome problems that occur related to the need for cheap information technology and reliable data file management.